THE EFFECTIVENESS OF MULTIMEDIA-BASED INQUIRY LEARNING MODELS IN ELEMENTARY SCHOOL LEARNING - Risnawati Yusuf; Sri Ayulinansyah (International Journal of Teaching and Learning, 2024)
The Inquiry Learning Model is a problem-based learning or investigation carried out by searching for truth or knowledge that requires critical, creative thinking and the ability to use intuition. Inquiry learning is a learning pattern to help students learn to formulate problems and test their own opinions and have awareness of their abilities. Learning begins with posing a problem and question. Students are required to think logically, analytically and critically in searching for, investigating and finding answers to the problems in question. The effectiveness of the inquiry learning model cannot be separated from the active role of students in the learning process. The learning material is not provided directly, but the role of students in this model is to search and find the learning material themselves, while the teacher acts as a facilitator and guide for students to learn. There are five stages taken in carrying out inquiry learning, namely: a) formulating problems to be solved by students; b) determine a temporary answer or better known as a hypothesis or problem; c) look for information, data and facts needed to answer hypotheses or problems; d) draw conclusions or generalizations; and e) draw conclusions.